HAZARDOUS NATURAL PHENOMENA: EARTHQUAKES AND MUDFLOWS - Vasliddinova Muslima (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article, written from the perspective of a 6th grade student from Uzbekistan, examines two of the most dangerous natural hazards — earthquakes and mudflows (sel). The author explains how these phenomena occur, what damage they cause, and what safety measures must be followed to protect human life and property. The article emphasises that awareness and correct behaviour during natural disasters can save lives.